The fiance dilemma eaudiobook A novel. - Armas, Elena (Green Oak, 2024)
A fake engagement, second chances, and newfound family members come together in this new romance from the New York Times bestselling author of the "swoon-worthy" ( Business Insider ) The Spanish Love Deception . Josie Moore has given the opposite sex—and love—plenty of chances. Four exactly, if you count all her failed engagements, and five if you include her no-longer-absentee father. Nonetheless, when the influential man decides to announce his retirement with a splashy magazine piece and Josie learns that her romantic history isn't great PR for the family, she jumps at the chance to offer a solution. Matthew Flanagan is in the mud. Literally. Not only has he been fired from his job, but after taking a wrong turn on his way to Green Oak, North Carolina, his car is stuck. So, he grabs a duffel bag with his essentials and goes in search of a place to crash until he gets his life (and vehicle) back on track. But instead, he stumbles upon his best friend's sister, Josie, greeting him as her fiancé. What starts as a big misunderstanding quickly turns into a fake engagement, with Matthew playing the role of the doting fiancé as he and Josie are swept into a PR whirlwind. The ring on Josie's finger makes her stomach turn, but she knows this is only temporary. They have rules in place, and one of them is that no matter what, there will be no exchange of "I dos." But that's easier said than done, as lines soon start to blur, and the rest of the small town comes to believe the fifth fiancé is truly The One.